Growing Environment and Heat Treatment Effects on Intra- and Interspecific Pollination in Chile Pepper (Capsicum spp.) - Tsung Han Lin; Shih Wen Lin; Yen Wei Wang; Maarten van Zonneveld; Derek W. Barchenger (Agronomy, 2021)
Heat tolerance is important for the sustainable production of many crops, including chile pepper. Tolerance to high temperature is complex and involves various component traits, with pollen viability being among the most important. in vitro pollen assays for heat tolerance have been widely used in chile pepper; however, associations between the pollen treatment and pollination have not been widely explored. The objectives of this study were to validate the utility of in vitro heat stress pollen characterization through in vivo pollination during summer and winter seasons and to evaluate the cross-compatibility among wild and domesticated species to initiate introgression population development. Seven entries of wild and domestic Capsicum species grown during the summer and winter seasons were used to evaluate pollination success rate. Pollen was either used directly or treated at 38 °C for four hours before making reciprocal self- and cross-pollination among all the entries. Significant associations between in vitro pollen treatment and pollination success rate during summer and winter seasons were identified. Heat treatment was a greater contributor to variability than the growing environment, which validates previous reports on the usefulness of studying pollen in vitro in selection for heat tolerance. Accessions of the wild progenitor C. annuum var glabriusculum, PBC 1969 and PBC 1970, were identified as a potential heat-tolerant source for use in breeding and future research. This work provides a basis for future research in exploring additional heat tolerance components as well as for the development of phenotyping assays for pollen or other floral traits.